PANDANGAN ISLAM TENTANG ILMU PENGETAHUAN DAN REFLEKSINYA TERHADAP AKTIVITAS PENDIDIKAN SAINS DI DUNIA MUSLIM - Hasbi Indra (State Islamic University North Sumatra, 2009)
Abstract: Islamic Perspective on Knowledge and its Reflection on Science Education Activities in the Muslim World. The holy book of Islam, the Qur’an, is very clear about its support for scientific enterprises. This is supported further by the traditions of the Prophet Muhammad SAW. This strong doctrinal foundation found its historical manifestations in the so-called the golden age of Islam, where sciences flourished in the Muslim kingdoms. However, by the end of the medieval period, the Muslim zeal for sciences weakened for several reasons, which according to the writer resulting in the present day backwardness of Muslim countries in general in almost all branches of scientific activities. This paper attempts to discuss how knowledge and science are perceived by Islam and their implication for science education.Kata Kunci: Islam, ilmu pengetahuan, dan peradaban